Use of Social Media Sites by Malaysian Universities and its Impact on University Ranking - Irfan, Asmara; Rasli, Amran; Sulaiman, Zuraidah; Sami, Abdul; Qureshi, Muhammad Imran (International Journal of Engineering and Technology, 2018)
Social Media is not just for photo sharing and status update, it can also be used by students for university selection. In the current era of high competition among higher educational institutes, many universities are focusing on online marketing. Most of the students are using social media sites to select their university which shows the importance of online presence for the universities. It is very much important for the universities to decide their marketing strategy to attract more and more international students. Good promotional marketing activities through social media, social networking sites by universities is associated with the ranking of the university. In this article we review the importance of social media marketing through social networking sites like Facebook and the capability of Malaysian universities to use social networking sites and its impact on university ranking and its Facebook engagement rank.